Studi Alkalisasi Serat Tandan Kosong Kelapa Sawit Sebagai Penguat Komposit Material Akustik. - Meilina, Putri; Haryanti, Ninis Hadi; Manik, Tetti Novalina (Universitas Lambung Mangkurat, 2024)
The use of empty oil palm fruit bunches as reinforcement in making composite boards has been carried out. Palm oil empty bunch fiber was obtained in the Kotabaru area, South Kalimantan. Palm oil empty fruit bunch fiber is hydrophilic which causes low adhesive properties between the fiber and the matrix so it is necessary to alkalize with 3% NaOH for 5 hours first. Alkalization has increased the cellulose content by 19.36% and reduced the lignin component by 9.04% and other components, such as hemicellulose, pectin, fat and others by 59.63%. Making composite boards uses the hand lay-up method and has succeeded in improving physical and mechanical properties. Water content according to SNI. The acoustic performance of composite boards shows significant results. The acoustic properties of composite boards without alkalization are sound absorbing, while with alkalization they are reflective. These results are supported by FTIR and SEM morphology results, which show that the interfacial bonding properties between the fiber and the matrix increase, thereby changing the acoustic performance of the TKKS composite board.Keywords: Alkalization, hand lay-up, acoustic performance, absorption, reflection.